PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK ETAP PADA PETERNAKAN AYAM (STUDI KASUS PADA PETERNAKAN AYAM IAN) - B51112057, Muhammad Rizky (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Biological assets are plants and animals that have biological transformations. Biological transformation consists of a process of growth, degeneration, production and procreation that cause qualitative and quantitative changes in animal and plant life. This research was conducted at the Chicken Farms Ian that engaged in the field of animal farms. The purpose of this study was to determine the application of the biological asset accounting and the presentation of the financial statements, and how the preparation of financial statements in accordance with SAK ETAP. This research used descriptive method. The data collection was conducted by interviews and direct observation to the farm owners. The results of this study indicated that the animal's biological assets like chicken as inventory with accounts chicken DOC, measured based on market value and presented on the balance sheet. The results of the preparation of financial statements did an income statement, statement of owner equity and the balance sheet. The financial statements are prepared based SAK ETAP and prepared in accordance with accounting cycle. Keywords: Biological Assets, Financial Statements, SAK ETAP